Inhaled dry powder mannitol in cystic fibrosis: an efficacy and safety study - Bilton, D.; Robinson, P.; Cooper, P.; Gallagher, C.G.; Kolbe, J.; Fox, H.; Jaques, A.; Charlton, B. (The European respiratory journal, 2011)
This international phase III study of inhaled dry powder mannitol was a randomised, double-blind, 26-week study, followed by a further 26-week, open-label (OL) extension. 324 cystic fibrosis (CF) patients were randomised, in a 3:2 ratio, to mannitol (400 mg b.i.d. ) and control groups. The primary efficacy end-point was to determine the change in forced expiratory volume in 1 s (FEV 1 ) over the double-blind phase. Secondary end-points included changes in forced vital capacity and pulmonary exacerbations. A significant improvement in FEV 1 was seen over 26 weeks (p<0.001) and was apparent by 6 weeks, irrespective of concomitant recombinant human deoxyribonuclease (rhDNase) use. At 26 weeks, there was a significant improvement in FEV 1 of 92.9 mL for subjects receiving mannitol compared with controls (change from baseline 118.9 mL (6.5%) versus 26.0 mL (2.4%); p<0.001). Improvements in FEV 1 were maintained up to 52 weeks in the OL part of the study. There was a 35.4% reduction in the incidence of having an exacerbation on mannitol (p=0.045). The incidence of adverse events (AEs) was similar in both groups, although treatment-related AEs were higher in the mannitol compared with the control group. The most common mannitol-related AEs were cough, haemoptysis and pharyngolaryngeal pain. Mannitol showed sustained, clinically meaningful benefit in airway function in CF, irrespective of concomitant rhDNase use. Mannitol appears to have an acceptable safety profile for patients with CF.